2011
DOI: 10.3892/mmr.2011.705
|View full text |Cite
|
Sign up to set email alerts
|

Differential blood lipid-lowering effects of alkylsulfonated chitosan of different molecular weights in Syrian hamsters in vivo

Abstract: Abstract. This study investigated the effects of alkylsulfonated chitosan of different molecular weights on intestinal lipid absorption, blood lipid profiles and circulating adhesion molecules. Syrian hamsters were fed an AIN-93G-based high-fat diet (HFD) and were orally administered 5 or 10 mg/kg BW of oligomer (6 kDa) chitosan (OC), low-molecular-weight (70 kDa) chitosan (LMC) or high-molecular-weight (200 kDa) chitosan (HMC) four times per week for 12 weeks. Animals receiving 2.5 mg/kg BW lovastatin (LOVA) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Previous studies have demonstrated that the hydrolyzed products of chitosan (chitosan oligosaccharide) have biological activities, but the majority of these studies are in vitro or treated in animals via intravenous or intraperitoneal administration ( 26 28 ). In our primary studies, chitosan was demonstrated to have hypolipidemic effects which partly involved the suppression of intestinal lipid absorption and hepatic acyl coenzyme A:cholesterol acyltransferase-2 expression ( 29 ), and chitosan slowed down the rate of tumor growth; however, it did not inhibit tumor formation ( 29 ). So far, there is no available information on if chitosan affects immune responses in leukemia mice.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that the hydrolyzed products of chitosan (chitosan oligosaccharide) have biological activities, but the majority of these studies are in vitro or treated in animals via intravenous or intraperitoneal administration ( 26 28 ). In our primary studies, chitosan was demonstrated to have hypolipidemic effects which partly involved the suppression of intestinal lipid absorption and hepatic acyl coenzyme A:cholesterol acyltransferase-2 expression ( 29 ), and chitosan slowed down the rate of tumor growth; however, it did not inhibit tumor formation ( 29 ). So far, there is no available information on if chitosan affects immune responses in leukemia mice.…”
Section: Discussionmentioning
confidence: 99%
“…Although numerous studies have shown that chitosan is able to inhibit the growth of microbial organisms ( 7 11 ), it has also been shown to cause significant downregulation of the expression of pro-inflammatory markers CD86 and MHCII on macrophages, decrease the expression of the pro-inflammatory cytokine TNF-α and increase that of the anti-inflammatory cytokines IL-10 and TGF-β1 ( 12 , 13 ). In addition, our earlier study has shown that the hypolipidemic effect of chitosan is partly attributed to its suppression of intestinal lipid absorption and hepatic acyl-coenzyme A: cholesterol acyltransferase-2 expression ( 18 ). Furthermore, chitosan has also been found to slow down the rate of tumor growth without inhibiting tumor formation ( 14 ); however, no detailed analysis of the immune responses in chitosan-treated animals, including mice, has been reported.…”
Section: Discussionmentioning
confidence: 99%